Climate Change in Digital Transformation: An Analytical Study for Sumer University Leaders - Sarah Saad Abdul Hadi Obaid; Tariq Kazim Shalaka (International Forum of Researchers and Lecturers, 2025)
This research aims to analyze the impact of change leadership on the digital transformation of universities through strategic capabilities as an intermediary factor, highlighting Sumer University as a model for the study. The study focused on diagnosing the reality of the application of change leadership and the university's readiness for digital transformation, in addition to measuring the relationship between these variables. The research relied on the descriptive analytical approach and the size of the community was (284) in (9) colleges of Sumer University, which included a random sample of 161 leaders at Sumer University (the university president, the university president's assistant, the dean, the assistant dean, the head of the department, and the division director). A questionnaire was designed as the main tool for collecting data, based on solid measures on the research variables (change leadership, digital transformation) with the results analyzed using SPSS and Amos software. The research concluded the importance of enhancing change leadership as a means of improving digital transformation and developing university performance. Statistical methods were used, including (validity and reliability test, normal distribution test, confirmatory factor analysis, mean, standard deviation, coefficient of variation, relative importance, Pearson correlation coefficient, simple linear regression, etc.) to test the main and sub-hypotheses of the research. A set of conclusions were reached, the most important of which is that the dimensions of change leadership play an effective and influential role in one of the dimensions of digital transformation, which is digital leadership in general